2010
DOI: 10.1681/asn.2009121302
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus Therapy to Halt the Progression of ADPKD

Abstract: Activation of mammalian target of rapamycin (mTOR) pathways may contribute to uncontrolled cell proliferation and secondary cyst growth in patients with autosomal dominant polycystic kidney disease (ADPKD). To assess the effects of mTOR inhibition on disease progression, we performed a randomized, crossover study (The SIRENA Study) comparing a 6-month treatment with sirolimus or conventional therapy alone on the growth of kidney volume and its compartments in 21 patients with ADPKD and GFR Ն40 ml/min per 1.73 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
119
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(127 citation statements)
references
References 40 publications
4
119
0
3
Order By: Relevance
“…The association between baseline TKV and baseline iothalamate clearance (GFR) was modestly significant in 241 participants (r=2 0.39, P,0.001), However, only 29 participants reached stage 3 CKD (GFR of 60 ml/min per 1.73 m 2 ), and only those with the largest kidneys (.1500 cc) demonstrated a significant decline in GFR (24.33 ml/min per yr) in the first 3 years of follow-up (4). Results from three recent prospective clinical trials of relatively short duration have not demonstrated an association between changes in TKV and GFR (23)(24)(25), questioning the value of TKV as a disease marker in ADPKD (26). We present the results of 8 years of follow-up in study participants to determine the extent to which baseline TKV predicts the future development of renal insufficiency.…”
Section: Introductionmentioning
confidence: 97%
“…The association between baseline TKV and baseline iothalamate clearance (GFR) was modestly significant in 241 participants (r=2 0.39, P,0.001), However, only 29 participants reached stage 3 CKD (GFR of 60 ml/min per 1.73 m 2 ), and only those with the largest kidneys (.1500 cc) demonstrated a significant decline in GFR (24.33 ml/min per yr) in the first 3 years of follow-up (4). Results from three recent prospective clinical trials of relatively short duration have not demonstrated an association between changes in TKV and GFR (23)(24)(25), questioning the value of TKV as a disease marker in ADPKD (26). We present the results of 8 years of follow-up in study participants to determine the extent to which baseline TKV predicts the future development of renal insufficiency.…”
Section: Introductionmentioning
confidence: 97%
“…After observational findings that, in patients with ADPKD receiving a kidney transplant, cyst growth was slowed by sirolimus-based immunosuppressive therapy (4), a pilot, prospective, randomized, crossover trial found that 6-month sirolimus therapy, unlike conventional therapy, halted the growth of total cyst volume in 15 patients with normal renal function or mild to moderate renal dysfunction (9). However, two subsequent large clinical trials (10,11) failed to show a clear beneficial effect of either sirolimus or everolimus in patients with CKD stages 2-3b renal function.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials testing the efficacy of mTOR inhibitors were recently evaluated. [13][14][15][16][17][18][19] mTOR plays a central role in regulating cell growth by integrating signals from growth factors, nutrients, and cellular energy levels. mTOR is a serine/threonine kinase that forms two distinct physical and functional complexes, TOR complex 1 (TORC1) and TOR complex 2 (TORC2).…”
mentioning
confidence: 99%